Pembagian Harta Bersama Pasca PerceraianPasangan Berbeda Kewarganegaraan: Perbandingan Hukum Indonesia dan Belanda - Ditasya Aulia Putri; Natasya Yunita Sugiastuti (Reformasi Hukum Trisakti, 2023)
This study examines the separation of marital property after divorce between mixed married couples. It compares Indonesian and Dutch laws on the division of matrimonial property upon divorce, focusing the case of Henk Willem van Der Spil (a Dutch citizen) and Dyah Supriyantini (an Indonesian citizen). The study shows how the two legal systems are alike and different The research type is normative and descriptive, utilizing secondary data, qualitative analysis, and a comparative legal approach with deductive conclusions. The findings display similarities: 1) Research considers the division of shared belongings among couples in mixed marriages according to the HPI factors; 2) Both the Indonesian and Dutch HPI designate Indonesian law as applicable. The variations include: 1) Under Indonesian law, land and buildings are not counted as community property, whereas Dutch law regards them as such and divides them equally. 2) Indonesian law excludes the income of the Tulips Hotel and Resto from community property, while Dutch law includes it. 3) The Dutch law recognizes "divorce covenant," a concept that is not present in Indonesian law. Recommendations: to achieve fairness, judges should. consider international civil law and foreign law aspects when dividing property in joint ownership between mixed marriage couples.